Workplace family support perception, work-family balance, job and family satisfaction among employed mothers and fathers in Chile - Riquelme-Segura, Leonor; Schnettler, Berta; Matias, Marisa; Concha-Salgado, Andrés; Orellana, Ligia; Sepulveda, José A. (Frontiers in Psychology, 2025)
IntroductionDual-income families with children face the challenge of balancing work and family to achieve greater wellbeing, especially in the context of the health emergency resulting from the COVID-19 pandemic. A quantitative methodology was used to examine the direct and indirect intraindividual and interindividual relationships between the workplace family support perception, work-family balance, and job and family satisfaction.MethodsThe study involved 454 couples of mothers and fathers of children between 12 and 16 years of age, workers from two regions in Chile. The questionnaires included the scales of perceived workplace support for families, work-family balance, job satisfaction, and family satisfaction.ResultsThe results provide new insights into the positive direct and indirect link between workplace family support perceptions, work-family balance, and satisfaction with work and family domains in mothers and fathers with paid work. In addition, they show the role of work-family balance as an underlying mechanism through which greater job satisfaction (at the intra- and interindividual level) and family satisfaction (at the intra- and interindividual level) would be possible.DiscussionNew insights are provided on the direct and indirect positive relationship with symmetrical crossovers in mothers and fathers between perceived workplace support for the family, work-family balance, job satisfaction, and family satisfaction.